TES DAN KONDISI FISIK ATLET KABADDI KABUPATEN LOMBOK BARAT - Diah Lukitasari; Noor Akhmad; Astrid Octavia Bahari; Fadli Zainuddin; Ali Muhaimin; Baiq Satrianingsih; Srisukarni Srisukarni (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
ABSTRACK The lack of objective data on athletes' physical condition has become one of the major challenges in the development of kabaddi in West Lombok Regency. This limitation prevents coaches from conducting evidence-based evaluations of athletes' physical abilities and designing training programs tailored to individual needs. This community service program aimed to conduct physical fitness testing and assessment of kabaddi athletes to establish baseline physical profiles for athlete mapping, training evaluation, and the development of data-driven training recommendations. The program employed a sport science approach consisting of coordination with stakeholders, preparation of equipment and testing instruments, participant orientation, physical fitness testing, data recording, descriptive analysis, and the delivery of recommendations to coaches and sport administrators. The assessment included anthropometric measurements, the Standing Broad Jump, Shuttle Run, 30-meter sprint, and the Bleep Test. The results showed that all testing procedures were successfully implemented, producing physical profiles of 37 athletes. The distribution of physical fitness levels was dominated by the moderate category (40.54%), followed by poor (29.73%), good (27.03%), and very poor (2.70%), while no athlete achieved the very good category. These findings provide objective baseline data that can be used for athlete evaluation, training program development, performance monitoring, and athlete selection. In addition, the program provided athletes and coaches with a better understanding of the importance of physical fitness assessment as an integral component of evidence-based athlete development. Overall, this community service program contributes to strengthening the implementation of data-driven and sport science-based kabaddi coaching in West Lombok Regency in a more systematic and sustainable manner. ABSTRAK Keterbatasan data objektif mengenai kondisi fisik atlet menjadi salah satu kendala dalam pembinaan cabang olahraga kabaddi di Kabupaten Lombok Barat. Kondisi tersebut menyebabkan pelatih belum memiliki dasar yang terukur dalam mengevaluasi kemampuan fisik atlet maupun menyusun program latihan yang sesuai dengan kebutuhan individu. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk melaksanakan tes dan pengukuran kondisi fisik atlet kabaddi sebagai dasar pemetaan kemampuan fisik, evaluasi pembinaan, dan penyusunan rekomendasi program latihan berbasis data. Metode yang digunakan berupa pendekatan sport science melalui tahapan koordinasi dengan mitra, persiapan alat dan instrumen, sosialisasi, pelaksanaan tes kondisi fisik, pencatatan hasil, analisis deskriptif, serta penyampaian rekomendasi kepada pelatih dan pengurus. Komponen yang diukur meliputi antropometri, standing broad jump, shuttle run, lari 30 meter, dan bleep test. Hasil kegiatan menunjukkan bahwa seluruh rangkaian tes terlaksana dengan baik dan menghasilkan profil kondisi fisik 37 atlet, dengan distribusi tingkat kebugaran yang didominasi kategori sedang (40,54%), diikuti kategori kurang (29,73%), baik (27,03%), dan kurang sekali (2,70%), sementara belum terdapat atlet yang berada pada kategori baik sekali. Profil kondisi fisik tersebut memberikan data objektif yang dapat dimanfaatkan sebagai dasar evaluasi, penyusunan program latihan, monitoring perkembangan atlet, dan proses seleksi. Selain itu, kegiatan ini memberikan pemahaman kepada atlet dan pelatih mengenai pentingnya evaluasi kondisi fisik sebagai bagian dari pembinaan olahraga prestasi. Kegiatan pengabdian ini berkontribusi dalam mendukung penerapan pembinaan kabaddi berbasis data dan sport science secara lebih sistematis dan berkelanjutan di Kabupaten Lombok Barat.